2011
DOI: 10.1038/nrmicro2690
|View full text |Cite
|
Sign up to set email alerts
|

Emerging molecular insights into the interaction between probiotics and the host intestinal mucosa

Abstract: Probiotic bacteria can modulate immune responses in the host gastrointestinal tract to promote health. The genomics era has provided novel opportunities for the discovery and characterization of bacterial probiotic effector molecules that elicit specific responses in the intestinal system. Furthermore, nutrigenomic analyses of the response to probiotics have unravelled the signalling and immune response pathways which are modulated by probiotic bacteria. Together, these genomic approaches and nutrigenomic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
414
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 569 publications
(425 citation statements)
references
References 164 publications
0
414
0
11
Order By: Relevance
“…The earliest research on probiotics dates back to 1907, when Metchnikoff claimed that the people administrated lactic acid-producing bacteria in yoghurt resulting in balance of intestinal micro-flora and longevity (Metchnikoff 1987;Bron et al 2012). It has been reported that administrated infant bifidobacteria could become the dominant of the intestinal micro-flora, reduce the putrefactive bacteria, and improve the immunity of the host (Tojo et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The earliest research on probiotics dates back to 1907, when Metchnikoff claimed that the people administrated lactic acid-producing bacteria in yoghurt resulting in balance of intestinal micro-flora and longevity (Metchnikoff 1987;Bron et al 2012). It has been reported that administrated infant bifidobacteria could become the dominant of the intestinal micro-flora, reduce the putrefactive bacteria, and improve the immunity of the host (Tojo et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A current survey of the literature indicates increased interest in understanding the cell surface molecules associated with probiotic action (Bron et al, 2012). The roles of sortase and SDPs have yet to be investigated in L. acidophilus, a commercial probiotic, or the human commensal L. gasseri.…”
Section: Discussionmentioning
confidence: 99%
“…These immunomodulatory capacities of probiotic strains have been extensively studied using various in vitro co-culture assays that employ different types of immune cells such as human monocyte-derived dendritic cells, human peripheral blood mononuclear cells and mouse bone-marrow-derived dendritic cells and use cytokine production profiles as a functional read-out. Interleukin-10 (IL-10) which is associated with T helper 2 (T H 2) cell or T regulatory (T Reg ) cell stimulation is typically used as a marker for antiinflammatory effects, whereas the p70 IL-12 heterodimer and tumor necrosis factor (TNF), which are associated with both T H 1 cell stimulation and the induction of interferon-γ (IFN-γ) production by T cells and natural killer (NK) cells, are commonly measured as markers for pro-inflammatory responses (Bron et al 2012).…”
Section: Production Of Antimicrobial Peptidesmentioning
confidence: 99%